(3GdeMGVQGJ (B((3aj GdCOH(B)s - (3GdMSf Hf eSYhO Hf eMeO, CHh Ydj, fhQ GdOjf GdjhSj,J (B1102 (3g` s
(3ChdgG (B:s
(3CeG HYO, aEf GdOgQ CHhGdYLGFH, hjfHhY GdZQGFH, haj GdeKd(B: "(3GdCjGe oMHdi dG JOQj eG JdO(B" s
(3BNQgG (B:s
(3hSjOj CHhGdbGSe Hf ehSi hGdGSJGP GdWGgQ GdTQja ced GdcJGH GdeHGQc HMeO Gddg s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B237 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B294s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B11 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG CQVg s
Keywords: (3GdCOHs